Role of Hemoperfusion With CytoSorb Associated With Continuous Kidney Replacement Therapy on Renal Outcome in Critically III Children With Septic Shock - Bottari, Gabriella; Lorenzetti, Giulia; Severini, Flavia; Cappoli, Andrea; Cecchetti, Corrado; Guzzo, Isabella (Frontiers in Pediatrics, 2021)
Introduction: Sepsis-associated acute kidney injury (SA-AKI) represents a relevant cause of mortality and morbidity in critically ill children. Since with the “inflammatory theory” the authors have been witnessed an important role of inflammatory mediators in the pathophysiology and in the prognosis of SA-AKI, making the need of adjunctive therapies in association with kidney replacement therapies mandatory. Hemoperfusion with CytoSorb is a safe and well-tolerated therapy in septic shock: the very high surface area of the absorber means it is able to efficiently remove cytokines and other medium size molecules involved in cytokine storm, thus playing a synergistic effect with Continuous Kidney Replacement Therapy (CKRT). Materials and Methods: We retrospectively analyzed data from a cohort of eight critically ill children treated from January 2018 to March 2020 describing the impact of CKRT plus hemoperfusion with CytoSorb on renal outcome in critically ill children with septic shock. Results: We evidenced a significant reduction in interleukin (IL)-6 an IL-10 after hemoperfusion with CytoSorb in our pediatric population. Furthermore, we were able to show a significant improvement of creatinine and blood urea nitrogen (BUN) after blood purification and at pediatric intensive care units (PICU) discharge. We have observed a median of 2.5 CKRT days after stop of hemoperfusion (Q1 0.25; Q3 18.75). None of our patients required CKRT 30 days after PICU discharge (PICU-D). None of them developed CKD. Conclusion: Hemoperfusion with CytoSorb is a valuable therapeutic option in combination with CKRT in SA-AKI. More studies are warranted to confirm our results and in particular to define the role of this adjuvant therapy as a preemptive strategy to protect renal function in pediatric septic shock.